2021
DOI: 10.1590/1984-0462/2021/39/2019296
|View full text |Cite
|
Sign up to set email alerts
|

Brazil’s Progress in Protecting, Promoting and Supporting Breastfeeding From the Perspective of the Global Breastfeeding Collective

Abstract: Objective: To identify and to discuss the progress of actions for the protection, promotion and support of breastfeeding in Brazil from the perspective of the indicators proposed by the Global Breastfeeding Collective. Data source: A narrative review was conducted according to the methodological orientation of the implementation research and through a qualitative approach. Publications from the World Health Organization and the United Nations Children’s Fund were selected, as well as publications from the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 5 publications
1
10
1
2
Order By: Relevance
“…Overall, our findings highlight the advantages of counselling and education activities when carried out simultaneously, either in the health system, community or at the individual level, as reported by various studies (Melo et al, 2021;Pérez-Escamilla et al, 2016;Sinha et al, 2015). Our analysis supports previous literature showing that needs-based, one-to-one, informal sessions delivered by trained personnel, including peer-counsellor, promoted breastfeeding practices (Thurston et al, 2013).…”
Section: These Interventions Can Potentially Be Replicated In Other A...supporting
confidence: 87%
See 1 more Smart Citation
“…Overall, our findings highlight the advantages of counselling and education activities when carried out simultaneously, either in the health system, community or at the individual level, as reported by various studies (Melo et al, 2021;Pérez-Escamilla et al, 2016;Sinha et al, 2015). Our analysis supports previous literature showing that needs-based, one-to-one, informal sessions delivered by trained personnel, including peer-counsellor, promoted breastfeeding practices (Thurston et al, 2013).…”
Section: These Interventions Can Potentially Be Replicated In Other A...supporting
confidence: 87%
“…The differences in the timing of rolling out each intervention throughout the BADUTA study might have resulted in the relatively modest results found in our trial despite implementing a package of interventions compared to studies implementing only a single intervention (Lassi et al, 2020 ). However, it is also plausible that multiple components of intervention working at different levels that worked synergistically to promote optimal breastfeeding practices will produce a larger effect than individual intervention alone, as reported in other studies (Melo et al, 2021 ; Pérez‐Escamilla et al, 2012 ).…”
Section: Discussionmentioning
confidence: 86%
“…In studies already mentioned, one carried out in Londrina -PR, in 2008, and another in Cruzeiro do Sul -AC, in 2015-2016.5% and 90% of children received breast milk in the first hour of life, respectively (RODRIGUES et al, 2021;SOUZA et al, 2012). The prevalence of breastfeeding in the first hour of life in the present study showed a value considered higher than the target stipulated by the 2019 indicators of the Global Breastfeeding Collective (GBC), a program led by WHO and Unicef, with the objective of universal improvement in terms of investments in AM, at least more than 70% for 2030 (MELO;PEREIRA, 2021).…”
Section: Discussioncontrasting
confidence: 56%
“…As a result, a National Policy for Breastfeeding Incentive was created in 1981, and marketing of infant food was regulated in 1988. 1 , 2 …”
Section: Introductionmentioning
confidence: 99%